Malignant Transformation in a Genitocrural Porokeratosis : A Case Report - Mrunali Joshi; Pooja Agarwal; Raju Chaudhary; Kalgi Baxi (Nepal Journal of Dermatology, Venereology & Leprology)
Porokeratosis is a rare heterogenous group of keratinization disorder with an unclear pathogenesis, and has varied clinical presentations. It may present with annular papules or plaques with central atrophy and clinically and histologically distinct ridge-like border called 'cornoid lamella'. Common variants include porokeratosis of Mibelli (PM), disseminated superficial actinic porokeratosis (DSAP), linear porokeratosis, punctate porokeratosis and porokeratosis palmaris et plantaris disseminata (PPPD). Here we report the case of a 79 year old female, who developed malignancy of porokeratosis over the groin region which had been mismanaged as eczema for many months and has been eventually diagnosed as Squamous cell carcinoma.